Factors Affecting The Performance Of Village Equipment In Giri Mulya District, Bengkulu Utara Regency - Wahyudi Al’azim; Ahmad Soleh; Rinto Noviantoro (Jurnal Fokus Manajemen, 2022)
The purpose of this study was to determine the factors that affect the performance of village officials in Giri Mulya District, North Bengkulu Regency. The sample in this study was 60 village officials in Giri Mulya District, North Bengkulu Regency. The data was collected using a questionnaire and the analytical methods used were multiple linear regression, determination test and hypothesis testing. Multiple regression test results show a positive direction with the regression equation Y = 1.168 + 0.263X1 + 0.288 X2 + 0.420X3. Variable X1 (motivation) has a significant effect on Y (performance). This can be seen from the significance value of 0.005 <0.05, it can be concluded that hypothesis 1 is accepted. Variable X2 (Leadership) has a significant effect on Y (performance) this can be seen from the significance value of 0.005 <0.05. it can be concluded that hypothesis 2 is accepted. Variable X3 (work environment) has a significant effect on Y (performance). This can be seen from the significant value of 0.000 <0.05, it can be concluded that hypothesis 3 is accepted. Simultaneous test results then H0 is rejected and Ha is accepted, between the independent variables, namely X1 (motivation), X2 (leadership), X3 (work environment), have a significant influence together on performance (Y) because the significant value is 0.000 smaller than 0.05.